A two-stage hydrogen compressor based on (La,Ce,Nd,Pr)Ni5 intermetallics obtained by low energy mechanical alloying - Low temperature annealing treatment - Talagañis, Basilio Andres (2009)
La0.67Ce0.19Nd0.08Pr0.06Ni5 was synthesized by low energy mechanical alloying. The AB5 was milled up to completion stage to reach the ﬁnal composition and appropriate particle size distribution and microstructure characteristics. Crystallite size, strain and sorption properties of as-milled samples were evaluated. After milling, La0.67Ce0.19Nd0.08Pr0.06Ni5 and previously obtained LaNi5 were annealed at 600 ºC for 24 h. An improvement in both microstructural and hydrogen sorption properties was found. Equilibrium hydrogen sorption properties were obtained and quantiﬁed in the 25–90 ºC range. From these results, a two-stage hydrogen compressor was proposed. In the ﬁrst stage, hydrogen is absorbed by LaNi5 at 575 kPa and 25 ºC and desorbed at 1365 kPa and 90 ºC. In the second stage, this ﬂuid is absorbed by La0.67Ce0.19Nd0.08Pr0.06Ni5 at 745 kPa and 25 ºC and desorbed at 2100 kPa and 90ºC. As a result, a global compression ratio of 3.65 is reached using this scheme.